PENGARUH KOMPETENSI KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA YAYASAN BINA INSAN MADANI SAWANGAN KOTA DEPOK - Aprilia, Sahroja; Septiowati, Rini (Journal of Research and Publication Innovation, 2024)
The purpose of this study was to determine the influence of competence and work environment on employee performance at Bina Insan Madani Foundation partially and simultaneously. The method used is quantitative method. Respondents in this study amounted to 58 people. Data analysis using validity test, reliability test, classical assumption test, regression test, correlation coefficient analysis, coefficient of determination analysis and hypothesis testing. The results of this study are Competence has a significant effect on employee performance with a detemination value of 31% and in the hypothesis test obtained tcount 5.017> ttabel 1.672 with a significance value of 0.000 <0.05. The work environment has a significant effect on employee performance with a determination coefficient value of 28.3% with the hypothesis test obtained tcount 4,703 > ttabel 1.672 with a significance value of 0.000 <0.05. Competence and Work Environment simultaneously have a significant effect on Employee Performance with the regression equation Y = 10292 + 0.379 X1 + 0,385 X2. The correlation value is 0.670, which means that the independent variable and the dependent variable have a strong level of relationship. with the dependent variable has a strong level of relationship. The coefficient of determination is 44.9%. Hypothesis testing obtained Fcount 22.432 > Ftabel 3.16, this is reinforced by the ρvalue of 0.000 <0.05. Thus, then H0 is rejected and H3 is accepted. This means that there is simultaneous significant influence between competence, work environment and employee performance at Bina Insan Madani Foundation Depok City.